2016
DOI: 10.1038/srep22282
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial growth of iridate pyrochlore Nd2Ir2O7 films

Abstract: Epitaxial films of the pyrochlore Nd2Ir2O7 have been grown on (111)-oriented yttria-stabilized zirconia (YSZ) substrates by off-axis sputtering followed by post-growth annealing. X-ray diffraction (XRD) results demonstrate phase-pure epitaxial growth of the pyrochlore films on YSZ. Scanning transmission electron microscopy (STEM) investigation of an Nd2Ir2O7 film with a short post-annealing provides insight into the mechanism for crystallization of Nd2Ir2O7 during the post-annealing process. STEM images reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…The in-plane epitaxial relationship was verified as CsW2O6 [11 _ 0] || YSZ [11 _ 0]. Note that this epitaxial relationship is identical to that of normal pyrochlore-type iridate films grown on YSZ (111) substrates [17,18]. In addition, Qx values between the film and substrate were identical, indicating that CsW2O6 films were coherently grown on the YSZ lattice.…”
Section: ■ Experimental Sectionmentioning
confidence: 82%
“…The in-plane epitaxial relationship was verified as CsW2O6 [11 _ 0] || YSZ [11 _ 0]. Note that this epitaxial relationship is identical to that of normal pyrochlore-type iridate films grown on YSZ (111) substrates [17,18]. In addition, Qx values between the film and substrate were identical, indicating that CsW2O6 films were coherently grown on the YSZ lattice.…”
Section: ■ Experimental Sectionmentioning
confidence: 82%
“…While significant experimental progress has recently been made in bulk A-227 compounds, 5, including the demonstration of all-in/all-out non-collinear magnetic order, 24,38 observation of giant magnetoresistance associated with metallic domain walls [34][35][36] and indication of Weyl semimetal phases, 18,37 there are only a few studies on thin film samples, [39][40][41][42][43] which is largely due to the great challenges in obtaining high quality films. Theoretical studies on pyrocholore iridate thin films have suggested a variety of emergent topological properties, including the quantized anomalous Hall conductance 44 and the correlated Chern insulator 45 that are otherwise not accessible in bulk samples.…”
Section: Introductionmentioning
confidence: 99%
“…These proposed heterostructures can be realized using modern thin film growth techniques such as molecular beam epitaxy or pulsed laser deposition, owing to the stable +4 valence of Ir and Ti, as demonstrated by the recent successful growth of the spin ice and the iridate thin films [26][27][28][29] . While the lattice mismatch between bulk spin ice and iridate compounds is comparatively small (1%), even a modest epitaxial strain can lift frustration in the spin ice layer 26 .…”
Section: Discussionmentioning
confidence: 99%